An Overview of Mental Health for Students During the Covid-19 Pandemic Period : (A Literature Review): Gambaran Kesehatan Mental Bagi Mahasiswa Selama Masa Pandemi Covid-19 : Suatu Kajian Kepustakaan - Nopianto Nopianto (Badnur Medisa Group, 2022)
The COVID-19 (Coronavirus Disease 2019) pandemic is an epidemic that occurs worldwide and causes a number of psychological and mental health reactions. The review to provide an overview and describe the mental health conditions of students during the Covid-19 pandemic as well as practical ways that can be used as references to manage student mental health for optimizing online learning. This research was conducted using the Literature Review method with a national literature search on Google Schoolar. Based on the results of a study of various journals on student mental health, it was found that pandemic conditions and changes in learning methods have the potential to disrupt students' mental health. In Conclusion is related to the emergence of stress that affects mental health, students need to manage personal mental health with internal and external support, such as increasing the spiritual side, doing healthy physical activities, forming positive thinking and feeling habits, and seeking support from the University and assistance professional.